8+3m-3=9m+12-5m

Simple and best practice solution for 8+3m-3=9m+12-5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+3m-3=9m+12-5m equation:


Simplifying
8 + 3m + -3 = 9m + 12 + -5m

Reorder the terms:
8 + -3 + 3m = 9m + 12 + -5m

Combine like terms: 8 + -3 = 5
5 + 3m = 9m + 12 + -5m

Reorder the terms:
5 + 3m = 12 + 9m + -5m

Combine like terms: 9m + -5m = 4m
5 + 3m = 12 + 4m

Solving
5 + 3m = 12 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
5 + 3m + -4m = 12 + 4m + -4m

Combine like terms: 3m + -4m = -1m
5 + -1m = 12 + 4m + -4m

Combine like terms: 4m + -4m = 0
5 + -1m = 12 + 0
5 + -1m = 12

Add '-5' to each side of the equation.
5 + -5 + -1m = 12 + -5

Combine like terms: 5 + -5 = 0
0 + -1m = 12 + -5
-1m = 12 + -5

Combine like terms: 12 + -5 = 7
-1m = 7

Divide each side by '-1'.
m = -7

Simplifying
m = -7

See similar equations:

| 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 | | 5x+35=86 | | 13=3(x-4)-(x-9) | | 76+6x=-11x-145 | | G(x)=2x+1 | | 0.5x+1.9=0.8x-0.2 | | (4x-9z)(3x+5z)= | | 7x-20=33 | | (x^6y^-3/z^-1)-5 | | 0.19x+0.2(x-4)=0.01(5x-2) | | kx^2+k=8x-2xk | | 4(x-3)+1=6x-2(4+x) | | 1.67u-1.67=1.25-.67 | | 1.5x=x+15 | | 0.12(y-7)+0.18y=0.10y-0.6 | | .9y-3.6=-.3y+3 | | 7x-7=8+6x | | 3(4y+4)=10 | | 28x+35=8x-27 | | 4m=(m+4)(2-m) | | 14x-2=-3x-18 | | 7.25x+5.4y=730 | | 5.7x-3.1(x+5)=5.04 | | -2x/3-2-3 | | -[3z-(5z+8)]=8+(1z+7) | | 15x-25=4x+2 |

Equations solver categories